L- bupivacaine ultrasound guided stellate ganglion block in cancer pain management - Ahmed Ali Ahmed Abdelhafez; Azza Fouad Abdu Omran; Ekram Hamed Mahmod; Khaled Ali Awad Elsamahy (Cairo : Ahmed Ali Ahmed Abdelhafez, 2016)
This study done to evaluate the efficacy and safety of ultrasound guided SGB in chronic cancer pain management suggested to be sympathetically mediated in head, neck or upper limb. The total number of selected patients was 58 patients. We used an ultrasound imaging device with a 13-16 MHz linear array probe for the lateral paracarotid in-plane technique. Head and neck sympathetic block evidenced by ptosis occurred in all patients. Meanwhile, upper extremity sympathetic block evidenced by increased temperature occurred only in 94.83% patients. None of patients developed complications
Thesis (M.Sc.) - Cairo University - National Cancer Institute - Department of Anaesthesia and Pain Relief
Issued also as CD
Keywords: Cancer pain management; Stellate ganglion block; Ultrasound guided